2008
DOI: 10.1007/978-1-59745-133-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Mosaicism in Neural Stem Cells

Abstract: Neural stem and progenitor cells (referred to here as NSCs), located in the proliferative zones of embryonic brains, can be seen undergoing mitosis at the ventricular surface. Mitotic NSCs can be arrested in metaphase and chromosome "spreads" produced to reveal their chromosomal complement. Studies in mice and humans have revealed a prominent developmental presence of aneuploid NSCs, whereas other chromosomal defects, such as interchromosomal translocations and partial chromosomal deletions/insertions, are ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The observed increase in L1 DNA copy number in the brain suggests elevated levels of endogenous L1 retrotransposition in brain. However, other non-mutually-exclusive mechanisms must be considered when accounting for these L1 copy number differences (195, 251). Indeed, formal proof of endogenous L1 retrotransposition in brain will require the characterization of new L1 insertions from individual neurons.…”
Section: Impact Of Mobile Elements On Mammalian Genomesmentioning
confidence: 99%
“…The observed increase in L1 DNA copy number in the brain suggests elevated levels of endogenous L1 retrotransposition in brain. However, other non-mutually-exclusive mechanisms must be considered when accounting for these L1 copy number differences (195, 251). Indeed, formal proof of endogenous L1 retrotransposition in brain will require the characterization of new L1 insertions from individual neurons.…”
Section: Impact Of Mobile Elements On Mammalian Genomesmentioning
confidence: 99%
“…We further conducted a karyotypic analysis that revealed an aneuploid karyotype in the majority of purified VSEL cells by fluorescence in situ hybridization. Although aneuploidy has long been associated with cancer, it has recently been observed in cultured pluripotent and neuronal stem cells as well as normal neuronal progenitors and primary cells from blastocysts, so that the tendency to generate aneuploid cells may be a normal feature of regenerative systems (23)(24)(25)(26). Even so, the aneuploid pro- ducts themselves are unlikely to make a long-term contribution to regeneration, and it is unsurprising that these cells are unable to expand in vitro.…”
Section: Cxcr4mentioning
confidence: 99%
“…Neural aneuploidy occurs to a similar extent in both neurons and glia (Rehen et al, 2005), is found phylogenetically from fish through humans (Kingsbury et al, 2006; Peterson et al, 2008; Rajendran et al, 2007; Rehen et al, 2001; Rehen et al, 2005; Yurov et al, 2005), and is present throughout the neuraxis, with no obviously distinguishable neuroanatomical patterns (Rehen et al, 2001; Rehen et al, 2005; Westra et al, 2008). Aneuploidy represents the first, proven form of DNA sequence alteration(s) present in normal neural cells, while making it likely that other phenomena associated with “genomic instability” could also be present.…”
Section: Introductionmentioning
confidence: 99%